(3GdHQgGf GdQGFb GdeNdU ef hQW GdeVGFbs - (3SdjeGf Hf eMeO Hf CMeO GdeMdj,J (B298 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeaQO HGdHgGA CeG HYO aEf HYV ef gPHJ GdOjGfI ChUGaI hChMjJ GdCNhI CfeGbI jSCdfi JUfja cJGH jJVef GYJbGO Cgd GdOjf s
(3BNQgG (B:s
(3hGdTQW GdQGHY Cf jbUO HCYeGdg hLg Gddg SHMGfg hdG jTQc HYHGOI QHI CgOkG hPdc GdENdGU s
(3hjJVef GYJbGO Cgd GdOjf ef GdeWQbjI GdehMOjf eeG hGab ePgH GdgGOi GdQSi (B298(3g`s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs